Design of the streaming processor architecture for microkernel controller and ALU - Anuar, Nuhairi (2015)
Media application such as 3D graphic processing, image processing, video decode and encode requires high rates of arithmetic operation per second. As an outcome of a decade long research, Stream Processor architecture, which is designed to exploit the characteristic of media processing was proposed. A few architectures of stream processor had been proposed and among the popular streaming processor architecture was Imagine Stream Processor. This project is focusing on implementing Imagine-based stream processor architecture on Altera Cyclone IV GX FPGA specifically for ALU Clusters and Microkernel Controller modules. This project report presents the literature reviews of books, theses and papers regarding stream processor architecture and its related use cases. This report also documents the complete project methodology taken in order to design a stream processor on the FPGA where the design of the Stream Processor is using RTL design methodology and System Verilog Language. This report also detailed the architectural design of the stream processor in Chapter 3. Furthermore, result and discussion of the experimental work involve in this project also reported in Chapter 4. The project report concluded that an FPGA-based stream processor is successfully designed and tested with specific image processing use cases. This project report also described possible enhancements possible on the stream processor design